POLITICAL BRANDING AKUN INSTAGRAM @ANIES BASWEDAN DALAM ISU PILPRES INDONESIA 2024 - Arnanda, Arnanda Nopriandika (SCIENTIA JOURNAL, 2023)
The emergence of Instagram as a new media has made many people take advantage of Instagram in several aspects of life, including as a medium of communication as well as a medium for marketing products or services, and media for political party campaigns and media for partitioning themselves for public figures and politicians. As was done by Anies Baswedan who is a presidential candidate in the 2024 Indonesian Presidential Election. Anies Baswedan branded himself through Instagram by displaying content related to daily activities and activities when he visited several regions in Indonesia. The formulation of the problem of this research is how the political branding of the Instagram account @aniesbaswedan in the 2024 Indonesian presidential election issue. The research conducted aims to determine the political branding of the Instagram account @aniesbaswedan in the 2024 Indonesian presidential election issue. This type of research is qualitative, using interpretive qualitative methods and approaches that used is direct content analysis. The data collection method in this study was Miles and Huberman with four stages consisting of data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that Anies Baswedan divides himself into four categories in his uploads on Instagram, the first category is an honest leader, the second category is a smart leader, the third category is a visionary leader, the fourth category is a leader who is able to become a trendsetter.